Transformation through Tourism : Harnessing Tourism as a Development Tool for Improved Livelihoods - Messerli, Hannah R. (Taylor and Francis, 2013)
Is tourism a viable development tool? While the number of tourist arrivals at developed and developing countries grows, the question continues to arise as to the true propoor impact of tourism. The purpose of this note is to highlight some examples of the World Bank’s recent work in tourism and explore possible approaches for the future.